2014
DOI: 10.5850/jksct.2014.38.3.293
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shopping Value on Fashion Shopping Satisfaction and Future Behavioral Intention in Fashion Social Commerce

Abstract: This study investigated the effect of consumers' shopping value in social commerce on consumers' fashion shopping satisfaction and future behavioral intention. Respondents were limited to consumers aged 20 to 39 who had recently purchased fashion products through social commerce over the last month. The final analysis used 318 samples. Descriptive statistics, Cronbach's alpha, confirmatory factor analysis, and structural equation model were conducted. The results are as follows. First, hedonic and utilitarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…As a result, consumers are actively expressing their preferences in social networks and consumers with similar preferences are forming clusters [84]. In addition, Yang and Choi [85] suggested that relationship characteristics must be intensified in order to increase the degree of WOM intention since consumers purchasing fashion products via social media actively communicate with their friends through SNS and emphasize mutual exchange through this use.…”
Section: Research Model and Research Hypothesismentioning
confidence: 99%
“…As a result, consumers are actively expressing their preferences in social networks and consumers with similar preferences are forming clusters [84]. In addition, Yang and Choi [85] suggested that relationship characteristics must be intensified in order to increase the degree of WOM intention since consumers purchasing fashion products via social media actively communicate with their friends through SNS and emphasize mutual exchange through this use.…”
Section: Research Model and Research Hypothesismentioning
confidence: 99%